DISCURSOS E PRÁTICAS FUNDAMENTALISTAS NA IGREJA PRESBITERIANA DO BRASIL (2002-2008) UMA ANÁ-LISE DA PRETENSA POSIÇÃO DE EQÜIDISTÂNCIA DOS EXTREMOS FUNDAMENTALISTAS E LIBERAIS - Souza, Robson da Costa de (2009)
In several occasions, Presbyterian Church of Brazil s leaders have revealed the desire of equal distance between fundamentalist and liberal extremes. However, the discourses and practices of this ecclesiastical institution contrast with this official positioning. Moreover, such assumed position of equal distance between fundamentalist and liberal extremes does not denote strict boundaries, but it is an effective device for legitimizing power at moments of changes in religious field, mainly in situations of internal crises. Likewise, after redemo-cratization of Brazil and the consequent increase of religious pluralism, there was a change in Brazilian social field, causing difficulties in more conservatives sections of this institu-tion. Nowadays, it is sought to revitalize religious tradition before the threats of dissolution which was imposed by modern process of emancipation and by secular and supposedly atheistic conceptions of life (such as feminism, the fight in defense of reproductive rights, civil union between same-sex people, the so called ―movement of lesbian, gays, bisexuals, transvestites and transgenders, etc.). In religious field, the immediate results of that attitude of reaction before social changes which was imposed by modernity are: (1) misogyny; (2) manifestation of religious-political activism in a conservative way that is, Protestants with fundamentalist trend, whose expansion in Brazil are growing decades ago in a very known speedy rhythm, based on a pattern of successful proselytism among the poorest layer of Brazilian population, throughout domestic territory.(AU)